Implementasi Kitab Al-Arabiyyah Bin-Namazij dalam Pembelajaran Bahasa Arab Kelas XI IPK 1 Pondok Pesantren Al-Ittifaqiah Indralaya - Thia Razimona Thia (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2024)
The goal of language teaching is to develop communicative competence in a language. In terms of the objectives of Arabic language learning, there are two aspects: receptive and productive. Receptive aspects involve receiving or absorbing information, such as listening and reading. Meanwhile, productive aspects involve producing language, both orally and in writing, as seen in speaking and writing activities. To achieve the goals of Arabic language teaching, many aspects must be considered. One supporting aspect of successful language teaching is the learning resources used. The book Al-Arabiyyah bin-Namazij is one of the books used by teachers in the Arabic language learning process at Al-Ittifaqiah 1 Islamic boarding school to support the achievement of learning objectives. This study aims to (1) determine the implementation of the Al-Arabiyyah bin-Namazij book in Arabic language learning (2) to determine the strengths and weaknesses of the Al-Arabiyyah bin-Namazij book in Arabic language learning. This research is a qualitative descriptive study with data collection techniques in the form of observation, documentation, and interviews. This study uses Miles and Huberman's data analysis model. Data analysis techniques include data reduction, data presentation, and conclusion drawing, with data validity checking through triangulation techniques. The results of this study indicate that the implementation of the Al-Arabiyyah bin-Namazij book is effective because it can facilitate teachers in delivering material, thus impacting students' learning outcomes. Teachers use eclectic methods, combining various methods in delivering instruction, including: deductive methods, lectures, discussions, and nahwu wa tarjamah methods. Among the strengths of the Al-Arabiyyah bin-Namazij book is the variety of examples included, which encourages critical thinking in students and also uses vocabulary and structures that are quite modern but easy to understand. In each chapter, there are motivational words for students in learning Arabic. Meanwhile, the weaknesses of this book emphasize the rules of nahwu and sharaf rather than the emphasis on everyday Arabic language skills. It is less suitable for beginners who are just starting to learn Arabic because the language used and the themes relate to the world of higher education.